Faktor-Faktor yang Mempengaruhi Kualitas Pelayanan Publik pada Kantor Kelurahan Klabinain Aimas Kabupaten Sorong Provinsi Papua Barat - Ida Ayu Putu Cindi Pratiwi; Widya Spalanzani; Yayan Saputra; Rifda Ilahy Rosihan; Ratih Kumalasari; Masjuli (Program Studi Teknik Industri, Fakultas Teknik, Universitas Bhayangkara Jakarta Raya, 2022)
Human resources or commonly referred to as HR is one of the important resources in a government and is often referred to as the spearhead to achieve goals in a government, as well as the facilities used in carrying out public services. Therefore, a government agency requires high-performing human resources and adequate facilities so that it can achieve the goals set by eachagencyrelated to carrying out public services. However, human resources and facilities at the Klabinain Village Office not very effective so that they have not been able to carry out public services properly. From this, the problem of this research is will examine the factors that affect the quality of public services at the Klabinain Aimas Village Office, Sorong Regency, West Papua Province. This research aims to determine whether or not the influence of human resources and facilities on the quality of public services at the Klabinain Aimas Village Office, Sorong Regency, West Papua Province. This research is a quantitative research. This researce was conducted for two months, namely November to December 2021.The sample in this study amounted to 123 people with the sampling technique using simple random sampling. Data collection techniques were carried out through questionnaires and literature study. Hypothesis testing using classical assumption test and simple regression analysis using the IBM SPSS Ver 26 application to determine the contribution of the independent variable to the dependent variable at the 95% trend level (α = 0.05). The results of the research are as follows: 1) there is no positive and significant influence between human resources on public services at the Klabinain Aimas Village office, Sorong Regency, West Papua Province. 2) there is no positive and significant effect between facilities and public services at the Klabinain Aimas Village office, Sorong Regency, West Papua Province.and 3) there is a significant effect between human resources and facilities if tested simultaneously on public services at the Klabinain Aimas Village office, Sorong Regency, West Papua Province.